Circulating and Hepatic BDCA1+, BDCA2+, and BDCA3+ Dendritic Cells Are Differentially Subverted in Patients With Chronic HBV Infection - Ouaguia, Laurissa; Leroy, Vincent; Dufeu-Duchesne, Tania; Durantel, David; Decaens, Thomas; Hubert, Margaux; Valladeau-Guilemond, Jenny; Bendriss-Vermare, Nathalie; Chaperot, Laurence; Aspord, Caroline (Frontiers in Immunology, 2019)
Background and aims: Chronic hepatitis B virus (HBV) infection is a major health burden potentially evolving towards cirrhosis and hepatocellular carcinoma. HBV physiopathology is strongly related to the host immunity, yet the mechanisms of viral evasion from immune-surveillance are still misunderstood. The immune response elicited at early stages of viral infection is believed to be important for subsequent disease outcome. Dendritic cells (DCs) are crucial immune sentinels which orchestrate antiviral immunity, which offer opportunity to pathogens to subvert them to escape immunity. Despite the pivotal role of DCs in orientating antiviral responses and determining the outcome of infection, their precise involvement in HBV pathogenesis is not fully explored. Methods: 130 chronically HBV infected patients and 85 healthy donors were enrolled in the study for blood collection, together with 29 chronically HBV infected patients and 33 non-viral infected patients were included for liver biopsy collection. In a pioneer way, we investigated the phenotypic and functional features of both circulating and intrahepatic BDCA1+cDC2, BDCA2+ pDCs and BDCA3+ cDC1 simultaneously in patients with chronic HBV infection by designing a unique multi-parametric flow cytometry approach. Results: We showed modulations of the frequencies and basal activation status of blood and liver DCs associated with impaired expressions of specific immune checkpoints and TLR molecules on circulating DC subsets. Furthermore, we highlighted an impaired maturation of circulating and hepatic pDCs and cDCs following stimulation with specific TLR agonists in chronic HBV patients, associated with drastic dysfunctions in the capacity of circulating DC subsets to produce IL-12p70, TNFα, IFNα, IFNλ1 and IFNλ2 while intrahepatic DCs remained fully functional. Most of these modulations correlated with HBsAg and HBV DNA levels. Conclusion: We highlight potent alterations in the distribution, phenotype and function of all DC subsets in both blood and liver, revealing that HBV may hijack the immune system by subverting DCs. Our findings provide innovative insights into the immuno-pathogenesis of HBV and the mechanisms of virus escape from immune control. Such understanding is promising for developing new therapeutic strategies restoring an efficient immune control of the virus.